Nomograph for Design of Channel Section Beams - Maitra, N. (Engineering Journal, 1975)
Channel sections are frequently used in the construction of operating platforms, passageways, stairs, etc. of industrial structures. They behave as beams and their moment of resistance for actual unbraced length must be calculated. The formulas used for channel sections are given in AISC Specification Sect. 1.5.1.4.6a. The value of d/Af (in these formulas) is available in manufacturers tables of properties for structural shapes as well as in the AISC Manual of Steel Construction. The value of Cb may be taken as unity for a simply supported system. For the convenience of designers, the AISC Manual of Steel Construction contains charts for determining the moment of resistance, MR, of wide flange beams when their unbraced lengths are known. However, no such charts are available for channel sections. A nomograph is presented herein for rapid determination of the values.